Portal vein thrombosis in pregnancy – a case series. (16th November 2010) - Anbazhagan, A; Harper, A; Bailie, C
Abstract : Portal vein thrombosis is rare in pregnancy. It is associated with thrombophilias, liver cirrhosis, abdominal infections and myeloproliferative disorders. The hypercoagulable state of pregnancy itself can precipitate this condition. The incidence of spontaneous abortion, prematurity, SGA babies and perinatal death are high. Long term anticoagulation and timely recognition and management of complications is the key to management. Here the authors present a case series of 3 pregnant women with portal vein thrombosis, and its associated complications namely portal hypertension, hypersplenism, thrombocytopenia, oesophageal varices and ascites that were successfully managed by a multidisciplinary team of specialists. All three women presented with the condition diagnosed prior to pregnancy. In one of them the cause was idiopathic and the other two resulted from thrombophilia (protein S deficiency and Factor V Leiden mutation). They had fortnightly antenatal checks, serial fetal well-being scans, prophylactic betamethasone for fetal lung maturity and treatment with propranolol, spironolactone and clexane. Two of them needed oesophageal banding during pregnancy. The three women were delivered by uncomplicated elective caesarean section at 38, 32 and 31 weeks of gestation respectively. The mothers and babies were discharged home in good health following an uneventful puerperium.